A Case of Choanal Polyp Originating From the Superior Nasal Concha - Mehmet Kelles; Israfil Orhan; Selman Sarica; Mehmet Fatih Inci (Medicine Science, 2013)
Almost all nasal polyps orginate from the mucosa of the lateral walls of the nasal cavity or from the paranasal sinuses. Diagnosis of a choanal polyp is made by endoscopic and radiologic examinations. Computed tomography and magnetic resonance imaging are very helpful to detect the origin and the extent of the polyp . Functional endoscopic surgery is the treatment of choice. Nasal polyps orginating from the superior nasal concha with choanal extension are extremely rare. We report a case of choanal polyp that arised from the superior nasal concha and extended down to the choana with its radiologic and surgical findings. [Med-Science 2013; 2(2.000): 624-7]